A Targeted Nano Drug Delivery System of AS1411 Functionalized Graphene Oxide Based Composites. Issue 4 (19th February 2021) - Liu, Baoqing; Yang, Wenzhi; Che, Chengchuan; Liu, Jinfeng; Si, Meiru; Gong, Zhijin; Gao, Ruixia; Yang, Ge
Abstract: A novel method for the preparation of antitumor drug vehicles has been optimized. Biological materials of chitosan oligosaccharide (CO) and γ‐polyglutamic acid (γ‐PGA) have previously been employed as modifiers to covalently modify graphene oxide (GO), which in turn loaded doxorubicin (DOX) to obtain a nano drug delivery systems of graphene oxide based composites (GO‐CO‐γ‐PGA‐DOX). The system was not equipped with the ability of initiative targeting, thus resulting into toxicity and side effects on normal tissues or organs. In order to further improve the targeting property of the system, the nucleic acid aptamer NH2 ‐AS1411 (APT) of targeted nucleolin (C23) was used to conjugate on GO‐CO‐γ‐PGA to yield the targeted nano drug delivery system APT‐GO‐CO‐γ‐PGA. The structure, composition, dispersion, particle size and morphology properties of the synthesized complex have been studied using multiple characterization methods. Drug loading and release profile data showed that APT‐GO‐CO‐γ‐PGA is provided with high drug loading capacity and is capable of controlled and sustained release of DOX. Cell experimental results indicated that since C23 was overexpressed on the surface of Hela cells but not on the surface of Beas‐2B cells, APT‐GO‐CO‐γ‐PGA‐DOX can target Hela cells and make increase toxicity to Hela cells than Beas‐2B cells, and the IC50 value of APT‐GO‐CO‐γ‐PGA‐DOX was 3.23±0.04 μg/mL. All results proved that APT‐GO‐CO‐γ‐PGA can deliver antitumor drugs in a targeted manner, and achieve the effect of reducing poison, which indicated that the targeted carrier exhibits a broad application prospect in the field of biomedicine. Abstract : A nano drug delivery system able to enhance active targeting and therapeutic efficacy has been reported. Nucleic acid aptamer NH2 ‐AS1411 (APT) of targeted nucleolin (C23) was used to conjugate on GO‐CO‐γ‐PGA to yield the targeted nano drug delivery system APT‐GO‐CO‐γ‐PGA. The structure, composition, dispersion, particle size and morphology properties of the synthesized complex were analyzed via multiple characterization methods to find high drug loading capacity, the ability of controlled and sustained release of drugs, and the targeting to Hela cells.